2012
DOI: 10.1122/1.3669647
|View full text |Cite
|
Sign up to set email alerts
|

The matching of a “one-dimensional” numerical simulation and experiment results for low viscosity Newtonian and non-Newtonian fluids during fast filament stretching and subsequent break-up

Abstract: This paper develops a model for fast filament stretching, thinning, and break-up for Newtonian and non-Newtonian fluids, and the results are compared against experimental data where fast filament relaxation occurs. A 1D approximation was coupled with the arbitrary Lagrangian Eulerian (ALE) formulation to perform simulations that captured both filament thinning and break-up. The modeling accounts for both the initial polymer stretching processes from the precise movement of the two moving pistons and also the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
33
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 45 publications
2
33
0
Order By: Relevance
“…Throughout we focus on the case of a highly viscoelastic filament of sufficiently large initial cross sectional area that surface tension can be safely ignored in comparison with the bulk viscoelastic stresses, at least in considering the initial stages of neck formation. In this way, we ignore any filament breakup and beading instabilities driven by surface tension [61][62][63][64][65].…”
Section: Introductionmentioning
confidence: 99%
“…Throughout we focus on the case of a highly viscoelastic filament of sufficiently large initial cross sectional area that surface tension can be safely ignored in comparison with the bulk viscoelastic stresses, at least in considering the initial stages of neck formation. In this way, we ignore any filament breakup and beading instabilities driven by surface tension [61][62][63][64][65].…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, we set the surface tension to zero in our calculations. We therefore do not address capillary breakup as studied in CaBeR rheometers [13,[37][38][39][40][41][42].…”
Section: Introductionmentioning
confidence: 99%
“…Study [16] demonstrated that a onedimensional long-wave model, as used in several of the above cited studies, exhibits good agreement with 2D axisymmetric computations. Therefore such computations have become a common approach when studying liquid jets and bridges [17].…”
Section: Introductionmentioning
confidence: 99%